ANALISIS TINGKAT KEPUASAN KARYAWAN TERHADAP KOMPENSASI YANG DIBERIKAN PT. SATRIA MULTI SUKSES, SEI TAKA ESTATE - Panado, Pilipus; Suyatno, Adi; Imelda, Imelda (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACT This study aims to analyze the level of employee satisfaction, the influence of compensation variables and which variables can affect the level of employee satisfaction, also to determine the position of each compensation variable to the level of employee satisfaction at PT. Satria Multi Sukses Sei Taka Estate. The method used in this study is the survey method. The research data was collected by distributing questionnaires to 49 selected respondents. Tests carried out in this study, there is a validity test, reliability test, satisfaction test index, interest performance analysis and performance satisfaction and importance of performance analysis. The results of this study indicate that employees of PT. Satria Multi Sukses Sei Taka Estate has been satisfied based on the level of satisfaction that is equal to 83.83 percent of the company's compensation variable. Variable positions included in quadrant A, where this is a performance that needs to be improved by PT. Satria Multi Sukses Sei Taka Estate is a variable work equipment. Keywords: level of employee satisfaction, employee compensation.